PENGARUH PEMBERIAN PEREGANGAN TERHADAP KELUHAN MUSKULOSKELETAL PADA PEKERJA PABRIK KERIPIK RUMAH ADAT MINANG DI DESA TADUKAN RAGA, DELI SERDANG - Tarianna Ginting; Rapael Ginting; Theresia Rianita Panjaitan; Delpitasari Marbun (Jurnal Darma Agung, 2020)
At the Minang Traditional House Chips Factory, located in Tadukan Raga Village, Deli Serdang, this still uses manual labor in its production. This of course can cause various health problems for workers such as musculoskeletal complaints which are influenced by non-ergonomic work postures,excessive use of energy.etc. This study aims to determine the effect of stretching on musculoskeletal complaints in workers of the Minang Traditional House Chips Factory in Tadukan Raga Village, Deli Serdang. This research method uses Quasi Experiment with Pre-Test and Post-Test designs. The sample of this study were 50 people. The statistical test used the Wilcoxon test with a significance level of α = 0.05. The results of statistical tests for the effect of giving muscle stretching on musculoskeletal complaints in workers showed that in 8 hours of work, the p value was obtained = 0.000 (p <0.05) and at 6 hours of work the p value was = 0.001 and 0.002 (p < 0.05). The conclusion of this study is that there is a significant effect of stretching on musculoskeletal complaints on workers of the Minang Traditional House Chips Factory in Tadukan Raga Village, Deli Serdang.